Determination of phenolic compounds in some almond hybrids varying in resistance to Pseudomonas amygdali - Misirli A.; Gülcan R.; Küden A.; Demir G. (XI GREMPA Seminar on Pistachios and Almonds, 2001)
Healthy young leaves were collected and analysed for their phenolic compound content in resistant and susceptible almond hybrids after artificial inoculation with Pseudomonas amygdali. Phenolic compounds were investigated by using spectrophotometry, thin layer and high-performance liquid chromatography. Consequently, average tannin content of medium resistant and resistant groups were higher than the others. When the phenolic compounds were investigated by using thin layer chromatography, some spots were determined only in resistant or in susceptible hybrids. In the analyses of phenolics by HPLC, chlorogenic acid content was found to be higher in the resistant hybrids.
11. GREMPA Seminar on Pistachios and Almonds, 1999/09/01-04, Sanliurfa (Turkey)